URGENSI MEMAHAMI BANUA MELALUI KAJIAN SOSIOLOGI AGAMA - Mujiburrahman Mujiburrahman (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
South Kalimantan, the original home of the Banjarese, is one of the most exclusively Muslim provinces in Indonesia. Therefore, in order to understand this region one should not only study the doctrines and rituals of Islam but also the manifestation of Islam in socio-cultural and political realities.The study of Islam in its social dimensions would provide us the ability to explain, predict and even to some extent control the religious tendencies in society. Based on current statistics and contemporary media reports, this paper presents a number of social issues related to religion that should be scientifically studied such as the historical development of Islam in the region, the role of the ulama, Islam and local culture, local politics and public rituals, drug abuses and the influences of the new media. These contemporary socio-religious issues are very important but still scarcely researched.